Effects of Some Dates, Pre -treatment Sowing, Soil Texture and Foliar Spraying of Zinc on Seedling of Dalbergia sissoo (Roxb.) - Ikbal M. Al-Barzinji; Sargul A. Khudhur; Nashat M. Abdulrahman (ARO-The Scientific Journal of Koya University, 2016)
Three experiments were conducted from the beginning of March to the end of October, 2012, in a field condition in Koya city-Iraqi Kurdistan region on shisham Dalbergia sissoo (Roxb.) trees. First experiment was laid out to study the effects of three date of sowing (15 of March, April and May), and six pre- treatments on seed germination of D. sissoo (Roxb.). The Results show that the best time of sowing for good seed germination was 15 of April. Highest germination rate was found when both sides of the pod were cut with soaking in tap water for 24 h. Second experiment was conducted to study the effects of three transplanting soil textures (clay, sandy and sandy clay (1:1) on seedling survival and some growth characteristics. Results indicates that D. sissoo gave better seedling survive rate, seedling leaves and height in sandy clay and sandy soils compared to clay soil. Third experiment was laid out to study the effects of foliar application of zinc (0, 57 and 114 ppm) sprayed on D. sissoo plants growing in clay, sandy and sandy clay (1:1) soils. Zinc application caused a significant increase in most vegetative growth characteristics. Treatments significantly increased leaves phosphorus, sulphate and zinc content compared to control. Most promising results were obtained from seedlings sprayed with zinc and grown in sandy clay soil.